2016
DOI: 10.1002/isaf.1392
|View full text |Cite
|
Sign up to set email alerts
|

Do Sentiments Matter in Fraud Detection? Estimating Semantic Orientation of Annual Reports

Abstract: SUMMARYWe present a novel approach for analysing the qualitative content of annual reports. Using natural language processing techniques we determine if sentiment expressed in the text matters in fraud detection. We focus on the Management Discussion and Analysis (MD&A) section of annual reports because of the nonfactual content present in this section, unlike other components of the annual reports. We measure the sentiment expressed in the text on the dimensions of polarity, subjectivity, and intensity and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 45 publications
3
66
0
Order By: Relevance
“…Furthermore, this model included adverbs as a key feature since a greater use of adverbs indicates the presence of fraud. The ma-chine learning model of Goel and Uzuner (2016), which includes nouns, verbs, adjectives and adverbs, corroborates this result. Fraudulent 10-K reports contain more adverbs and adjectives.…”
Section: Grammatical Featuressupporting
confidence: 71%
See 2 more Smart Citations
“…Furthermore, this model included adverbs as a key feature since a greater use of adverbs indicates the presence of fraud. The ma-chine learning model of Goel and Uzuner (2016), which includes nouns, verbs, adjectives and adverbs, corroborates this result. Fraudulent 10-K reports contain more adverbs and adjectives.…”
Section: Grammatical Featuressupporting
confidence: 71%
“…Fraudulent reports contain less positive words (Tatiana Churyk et al, 2008Lee et al, 2013Lee et al, , 2014. However, Goel and Uzuner (2016) showed that the fraudulent texts contain more positive and negative emotion words. Li (2010) drew a completely different conclusion.…”
Section: Psychological Process Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Goel and Uzuner () led a qualitative analysis of the text contained in reports for fraud detection by measuring the polarity, intensity, and subjectivity of the sentiment through management discussion and analysis. They found that a fraudulent report contains more positive and negative sentiments than a truthful report.…”
Section: Related Workmentioning
confidence: 99%
“…O'Leary (2015) underlined the importance of 'Twitter mining' by synthesizing the extant literature in using Twitter information for prediction, discovery and causation investigation. Goel and Uzuner (2016) led a qualitative analysis of the text contained in reports for fraud detection by measuring the polarity, intensity, and subjectivity of the sentiment through management discussion and analysis. They found that a fraudulent report contains more positive and negative sentiments than a truthful report.…”
Section: Previous Studies On Online Investor Sentimentmentioning
confidence: 99%